2014
DOI: 10.4102/curationis.v37i1.1281
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurse preceptors’ perceptions of benefits and support of and commitment to the preceptor role in the Western Cape Province

Abstract: The findings of this study are supported by Kanter's model of structural determinants of behaviour in organisations, since preceptors who see themselves as having access to opportunity and support are likely to be committed to their role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Given this background and the limited number of preceptors employed in South African hospitals, it can be argued that sufficient preceptor support by academically and clinically prepared nurses is still lacking and that the role of the preceptor is at present vague and needs clarification. This statement is consistent with the views of a number of researchers such as Cloete and Jeggels ( 2014 :6), Hofler and Thomas ( 2016 :135) and Morgan ( 2017 :23). Also, Quek and Shorey ( 2018 :420) assessed the perceptions of preceptorships of newly qualified nurses and found that in the Western Cape, South Africa, the perceived benefits and rewards for the preceptor role and a heavy workload had an impact on commitment to fulfil the preceptor.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Given this background and the limited number of preceptors employed in South African hospitals, it can be argued that sufficient preceptor support by academically and clinically prepared nurses is still lacking and that the role of the preceptor is at present vague and needs clarification. This statement is consistent with the views of a number of researchers such as Cloete and Jeggels ( 2014 :6), Hofler and Thomas ( 2016 :135) and Morgan ( 2017 :23). Also, Quek and Shorey ( 2018 :420) assessed the perceptions of preceptorships of newly qualified nurses and found that in the Western Cape, South Africa, the perceived benefits and rewards for the preceptor role and a heavy workload had an impact on commitment to fulfil the preceptor.…”
Section: Introductionsupporting
confidence: 89%
“…These are experienced often because of the lack of supervision and support, which can be provided by a preceptor. This statement has been supported by various researchers such as Cloete and Jeggels ( 2014 :2), Webster ( 2016 :2) and Zaayman ( 2016 :9), as well as by the comments, discussions and feedback made by colleagues in the clinical field of the hospitals and clinics. Additionally, the need for newly qualified nurses to be clinically and academically supervised and guided is crucial to guarantee that they can subsequently provide safe and competent care, which enables them to continuously grow in the profession from being novices to becoming experts.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations